2001
DOI: 10.4049/jimmunol.167.8.4368
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Pulmonary Fibrosis in the Absence of CCR2 Signaling

Abstract: Pulmonary fibrosis can be modeled in animals by intratracheal instillation of FITC, which results in acute lung injury, inflammation, and extracellular matrix deposition. We have previously shown that despite chronic inflammation, this model of pulmonary fibrosis is lymphocyte independent. The CC chemokine monocyte-chemoattractant protein-1 is induced following FITC deposition. Therefore, we have investigated the contribution of the main monocyte-chemoattractant protein-1 chemokine receptor, CCR2, to the fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
306
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 341 publications
(322 citation statements)
references
References 51 publications
13
306
3
Order By: Relevance
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…MCP-1 has previously been reported to be a major profibrotic chemokine involved in various fibrotic processes, including recruitment of fibrocytes, induction of collagen synthesis, and up-regulation of TGF-␤1 expression in various models. 50,51,[55][56][57][58][59][60][61][63][64][65][66][67][68] Indeed, we observed that MCP-1 responses preceded the responses of fibrogenic growth factor TGF-␤1, 51,52 which were significantly higher in the lung of infected TNF Ϫ/Ϫ lungs and were well correlated with fibrotic tissue remodeling seen in TNF Ϫ/Ϫ lungs at later time points during influenza infection. Thus, depletion of MCP-1 in influenza-infected TNF Ϫ/Ϫ hosts markedly reduced lung immunopathology and tissue remodeling, and such MCP-1 depletion-improved welfare was associated with diminished production of bioactive TGF-␤1.…”
Section: Discussionmentioning
confidence: 84%
“…51,[62][63][64][65][66][67][68] Thus, given the dysregulated MCP-1 and its association with heightened TGF-␤1 production seen in influenza-infected TNF Ϫ/Ϫ lungs (Figure 7), we further investigated the role of MCP-1 in heightened immunopathology and fibrotic reaction in the lung of TNF Ϫ/Ϫ mice by means of MCP-1 depletion. To this end, MCP-1 anti-serum (anti-MCP-1) or the control serum was administered intraperitoneally to TNF Ϫ/Ϫ mice on days 2, 5, and 9 following influenza infection, and the mice were sacrificed at day 21 after infection for morphometric quantification of lung immunopathology and fibrotic remodeling ( Figure 8A).…”
Section: Attenuation Of Lung Immunopathology In Influenza-infected Tnmentioning
confidence: 99%
“…8 Briefly, mice were anesthetized with sodium pentobarbital. The trachea was exposed and entered with a needle under direct visualization.…”
Section: Fitc Inoculationmentioning
confidence: 99%
“…9, 10 We previously demonstrated that mice that are deficient in CCR2 (CCR2 Ϫ/Ϫ mice) are protected from the development of experimental pulmonary fibrosis induced either by FITC or bleomycin. 8 However, recruitment of classical inflammatory cells (monocytes, macrophages, eosinophils, neutrophils, T, B, or NK cells) to the lung in response to FITC was not diminished when CCR2 Ϫ/Ϫ mice were compared to CCR2 ϩ/ϩ mice. 8 Because altered recruitment of classical inflammatory cells was not noted, we determined whether CCR2 played a role in mesenchymal cell recruitment to the lung in response to injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation